2009
DOI: 10.1063/1.3072022
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic orientation and the magnetocaloric effect in MnP

Abstract: Here we present results for single crystals of manganese phosphide (MnP), a material exhibiting a first-order ferromagnetic to paramagnetic transition at a Curie temperature of 290 K. MnP has a saturation field of about 7.5 kOe along the c-axis. Along this easy magnetic axis, ΔS was measured to be 2.2, 3.3, and 6.0 J/kg K in applied fields of 10, 20, and 50 kOe, respectively. The density of MnP is 5.49 g/cm3. No hysteresis or irreversibility was measured over a range of temperatures from 10 to 300 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In these systems, coupling of the spins and the lattice leads to a system with switchable magnetostructural state, so that a moderate magnetic field can induce a large change in the magnetic entropy of the system. 18,20,22 Inspired by these ideas, we propose here the use of computational screening to aid in discovery of new magnetocalorics. Recently, several high-throughput projects have used density functional theory (DFT) to calculate the total energies and electronic structures of hundreds of thousands of known and hypothetical materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these systems, coupling of the spins and the lattice leads to a system with switchable magnetostructural state, so that a moderate magnetic field can induce a large change in the magnetic entropy of the system. 18,20,22 Inspired by these ideas, we propose here the use of computational screening to aid in discovery of new magnetocalorics. Recently, several high-throughput projects have used density functional theory (DFT) to calculate the total energies and electronic structures of hundreds of thousands of known and hypothetical materials.…”
Section: Introductionmentioning
confidence: 99%
“…In Gd 5 (Si,Ge) 4 , a first-order coupled magnetic and structural transition leads to a greatly enhanced ∆S M . [19][20][21] After the discovery of this phenomena, several other systems with known first-order magnetostructural transitions were investigated, yielding some of the most promising magnetocaloric materials, including Fe 2 P-based and La(Fe,Si) 13 -based materials. In these systems, coupling of the spins and the lattice leads to a system with switchable magnetostructural state, so that a moderate magnetic field can induce a large change in the magnetic entropy of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese phosphide (MnP) is of fundamental interest due to its unique magnetic, magneto-optical, and magneto-caloric properties [1][2][3][4][5][6][7][8][9]. Particularly at the nanoscale, MnP structures have shown significantly different properties than bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Single crystal studies of MnP have shown that strong magnetocrystalline anisotropy leads to a greater MCE along the easy axis [11,12]. MnP is an attractive system for this study of magnetic anisotropy because its rich magnetic phase diagram has inspired a significant body of single crystal work.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of MnP is orthorhombic of space group Pnma with a ¼0.5260 nm, b¼0.3174 nm, and c¼ 0.5919 nm in the paramagnetic phase at 293 K, and a ¼0.5241 nm, b¼0.3181 nm, and c¼0.5903 nm in the ferromagnetic phase at 60 K [13]. MnP undergoes a ferromagnetic to paramagnetic phase transition at a Curie temperature of 290 K [11]. In this paper we follow the c4a 4b convention for the lattice parameters.…”
Section: Introductionmentioning
confidence: 99%